The Implementation of Partial Roya after Regulation of Minister of Agrarian & Spatial Planning - Muhammad Iqbal al Hakiem; Sri Endah Wahyuningsih; Dahniarti Hasana (Sultan Agung Notary Law Review, 2022)
This study aims to determine and analyze the authority of a Notary/PPAT in the implementation of partial roya after the enactment of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia No. 5 of 2020 concerning Electronically Integrated Mortgage Services. This research method uses a sociological juridical approach with descriptive research specifications. Data sources and data collection methods used primary and secondary data which were analyzed qualitatively. The results of this study indicate that the authority of a Notary/PPAT has an important role in the implementation of partial roya in the city of Semarang. The authority of the Notary/PPAT is the making of a credit agreement deed with a partial roya agreement, a roya concession deed if the mortgage certificate is lost, creation and registration of APHT with partial roya agreement and submission of roya application against conventional Mortgage Rights. Notaries/PPATs in carrying out their authority must comply with the applicable laws and regulations to ensure legal certainty. The implementation of partial roya at BPN Semarang City is currently divided into two, namely conventionally and electronically. The implementation of partial roya at BPN Semarang can be done without the need for prior agreement in the APHT. Partial roya on part of the result of splitting the parent certificate which is encumbered with Mortgage Rights can be made at BPN Semarang City on condition that it must be agreed upon by the creditor and debtor. The conclusion is implementation of partial roya using the electronic Mortgage system provides more benefits in terms of convenience and time efficiency.